Intra-testicular angioleiomyoma. A case report of a rare male urological entity - Afnan Elsayed, MD; Jaudah Al-Maghrabi, MD; Abdelrazak Meliti, MD, FRCPC (Urology Case Reports, 2022)
Angioleiomyoma (vascular leiomyoma) is a common benign smooth muscle tumor, often affecting the soft tissue of the extremities, head, and neck regions. However, testicular involvement is an exceedingly rare event. Herein, we present an unusual case of testicular angioleiomyoma. To the best of our knowledge, this is the third reported case in English literature.